Isolation and Characterization of Microsatellite Markers in the Southern Hake, Merluccius Australis - Vidal-Soto, R (2011)
Twenty-six nuclear-encoded microsatellites were isolated from an enriched genomic library of southern hake, Merluccius australis, and characterized in 30 individuals. The microsatellites include 18 dinucleotide repeats, seven trinucleotide repeats (two imperfect), and one pentanucleotide repeat. Southern hake support important industrial and artisanal fisheries in Chile, Argentina, and New Zealand. © 2010 Springer Science+Business Media B.V.